Human Leukocyte Antigen-Associated HIV-1 CRF02_AG gag and vif Polymorphisms in Ghana - Adusei-Poku, Mildred A.; Matsuoka, Saori; Bonney, Evelyn Y.; Abana, Christopher Z.; Duker, Ewurabena O.; Nii-Trebi, Nicholas I.; Ofori, Sampson B.; Mizutani, Taketoshi; Ishizaka, Aya; Shiino, Teiichiro; Kawana-Tachikawa, Ai; Ishikawa, Koichi; et al. (Japanese Journal of Infectious Diseases, 2019)
In human immunodeficiency virus type-1 (HIV-1) infections, cytotoxic T-lymphocyte (CTL) responses targeting human leukocyte antigen (HLA)-restricted viral epitopes exert strong suppressive pressure on viral replication and frequently select for mutations resulting in viral escape from CTL recognition. Numerous data on these HLA-associated mutations in HIV-1 subtypes B and C have been amassed with few reports described in other subtypes. In the present study, we investigated the HLA-associated mutations in HIV-1 subtype CRF02_AG prevailing in Ghana, Western Africa. We determined viral gag sequences in 246 out of 324 HIV-1-infected Ghanaians. Phylogeny analysis revealed that 200 (81.3%) individuals were infected with HIV-1 CRF02_AG. Full gag and vif sequences were obtained from 199 and 138, respectively, out of the 200 individuals infected with CRF02_AG and subjected to determination of HLA-associated mutations. The analysis found HLA-associated HIV-1 CRF02_AG non-synonymous polymorphisms at 19 sites; 13 in gag and six in vif, including those that were newly determined. Generation of this data is an important contribution to our understanding of HIV-1 CRF02_AG and host T cell interaction.